The influence of xylitol containing toothpaste on plaque formation inhibition on fixed bridge - Hamim Fithrony; Eha Djulaeha; Michel Soedjono (Dental Journal (Majalah Kedokteran Gigi), 2009)
Background: Plaque is the main cause of teeth and periodontal tissue damage, which usually accumulates on crown surfaces. To avoid this, plaque control is the best way that not only has a close connection to oral hygiene but also become important element in dental practice. Previously, xylitol was used as alternative sweetener for diabetic patients, but later it is used to maintain healthy teeth. Xylitol is capable to inhibit Streptococcus mutans growth which changes sugar and other carbohydrate into acid, because xylitol cannot be fermented. Purpose: This study was aimed to understand the inhibition capability of toothpaste containing xylitol to plaque formation on fixed bridge. Methods: This clinical experiment study was carried out in fifteen patients wearing fixed bridge at Prosthodontics Department, Faculty of Dentistry, Airlangga University in Surabaya from 2005 to 2008. Samples were based on selective random sampling technique. Plaque index was analyzed by Mann Whitney test. Result: This study showed that there was significant difference of plaque scores in patients who brush their teeth using xylitol containing toothpaste compared to the control group (placebo). Conclusion: Xylitol was capable to inhibit plaque formation on fixed bridge.